Chronic Inflammation and Age-Related Hearing: Based on Mendelian Randomization - Wang Y; Zhao H; Zhao K; He H; Li X; Qiu J; Cui L; Chen L; Shang W; Sun Y (Dove Medical Press, 2024)
Yan Wang,1- 4,* He Zhao,2- 4,* Kun Zhao,1- 4,* Huhuifen He,1- 4,* Xinyu Li,5 Jingjing Qiu,2- 4 Limei Cui,2- 4 Liang Chen,2- 4 Wenjing Shang,6,7 Yan Sun2- 4 1The Second Medical College, Binzhou Medical University, Yantai, Shandong, People's Republic of China; 2Department of Otolaryngology and Head and Neck Surgery, Yantai Yuhuangding Hospital, Qingdao University, Yantai, Shandong, People's Republic of China; 3Shandong Provincial Clinical Research Center for Otorhinolaryngologic Diseases, Yantai, Shandong, People's Republic of China; 4Yantai Key Laboratory of Otorhinolaryngologic Diseases, Yantai, Shandong, People's Republic of China; 5The First Medical College, Binzhou Medical University, Yantai, Shandong, People's Republic of China; 6Key Laboratory for Genetic Hearing Disorders in Shandong, Binzhou Medical University, Yantai, Shandong, 264003, People's Republic of China; 7Department of Biochemistry and Molecular Biology, Binzhou Medical University, Yantai, Shandong, 264003, People's Republic of China*These authors contributed equally to this workCorrespondence: Yan Sun; Wenjing Shang, Email entsunyan@126.com; wenjshang@bzmc.edu.cnIntroduction: Age-related hearing loss (ARHL) is a degenerative condition that involves both peripheral and central auditory system pathologies. There is a close relationship between chronic inflammation and ARHL, but there is currently a lack of in-depth exploration of this relationship, particularly regarding causality.Methods: Using age-appropriate mice for basic experiments to examine changes in central auditory nervous system inflammation, a cohort study was conducted to select relevant clinical data and observe inflammation changes in the elderly population with ARHL. Mendelian randomization was employed to investigate the causal relationship between chronic inflammation and ARHL.Results: Clinical results indicate that CRP levels in the ARHL group are significantly higher than those in the normal group. Chronic inflammation also occurs in the auditory centers. Mendelian randomization studies provide causal evidence that genetic chronic inflammation factors do not increase the risk of ARHL.Discussion: This article provides reliable causal evidence of the relationship between chronic inflammation and ARHL, confirming the accumulation of inflammatory factors in the auditory center, which provides a basis for the prevention and treatment of ARHL and has a good prevention prospect. However, due to the differences of research objects, this study has limitations and needs further research.Keywords: CRP, TNF-α, chronic inflammation, age-related hearing loss, Mendelian randomization